Police Sexual Violence: A Few Bad Apples or a Cultural Norm? - Bettinelli, Marta (2020)
Approximately 1,600 police officers across the United States were arrested for sex-related crimes during the ten year period 2005-2014. The arrested officers were employed by more than 1,100 state and local law enforcement agencies located in all fifty states and the District of Columbia. These data suggest that police sexual violence is a problem involving more than a few “bad apples” and that the phenomenon of police sexual violence may be a cultural norm within many state and local law enforcement agencies. This presentation was accepted for presentation at the annual meeting of the Academy of Criminal Justice Sciences in San Antonio, TX, on March 27, 2020. The conference, however, was cancelled due to the global COVID-19 pandemic